Optimizing the Role of Husbands in Childbirth Assistance through Education and Simulation of Nonpharmacological Techniques in Balikpapan - Nila Trisna Yulianti; Nurul Huda (Pengabdian: Jurnal Abdimas, 2026)
Background. Childbirth is a challenging experience, and the involvement of the husband in providing emotional and physical support can significantly impact maternal outcomes. However, paternal involvement in non-pharmacological labor support remains underexplored, particularly in Balikpapan. Purpose. This study aimed to optimize the role of husbands in supporting their wives during labor through education and simulation of non-pharmacological techniques. Method. The research employed a quasi-experimental design with a pre-test and post-test approach, involving 50 couples from Balikpapan. Participants attended educational sessions on non-pharmacological pain relief techniques, followed by simulation exercises where husbands practiced these methods. Results. The results showed a significant increase in husbands’ knowledge, with the mean post-test score rising from 35% to 78%. Moreover, husbands demonstrated a 60% improvement in applying non-pharmacological techniques during simulated labor scenarios. Conclusion. The findings suggest that targeted education and simulation effectively enhance husbands’ preparedness to provide essential support during labor, contributing to improved maternal comfort and reduced anxiety. This study highlights the importance of including paternal education in prenatal care programs, advocating for a more family-centered approach to childbirth. Future research should explore the long-term effects of such interventions and their applicability across diverse cultural contexts.